Daily and hourly patterns of physical activity and sedentary behavior of older adults: Atherosclerosis risk in communities (ARIC) study - Dooley, Erin E.; Pompeii, Lisa A.; Palta, Priya; Martinez-Amezcua, Pablo; Hornikel, Bjoern; Evenson, Kelly R.; Schrack, Jennifer A.; Pettee Gabriel, Kelley (Preventive medicine reports, 2022)
•Older adult activity patterns varied by day of the week with Sunday the least active.•Most physical activity was accrued during the morning hours (9 AM-12 PM).•Men and those with overweight and obesity had highest sedentary minutes.•Older adult movement patterns show opportunities for physical activity promotion. This cross-sectional study of older adults ≥ 65 years describes daily and hourly patterns of accelerometer-derived steps, sedentary, and physical activity behaviors and examines differences by day of the week and sociodemographic and health-related factors to identify time-use patterns. Data were from 459 Atherosclerosis Risk in Communities (ARIC) study participants (60% female; mean ± SD age = 78.3 ± 4.6 years; 20% Black) who wore a hip accelerometer ≥ 4 of 7 days, for ≥ 10 h/day in 2016. We used linear mixed models to examine daily patterns of steps, sedentary, low light, high light, and moderate-to-vigorous intensity physical activity (MVPA). Differences by sex, median age (</≥ 78 years), body mass index, self-rated health, depressive symptoms, and performance in a two-minute walk test were explored. Men (vs women), and those with overweight and obesity (vs normal weight), had significantly higher sedentary minutes and lower minutes of low light per day. For each additional meter walked during the two-minute walk test, sedentary behavior was lower while high light, MVPA, and daily steps were higher. No significant differences in time-use behaviors were found by self-reported race, age, education, self-rated health, or depressive symptoms. Participants were least active (22.5 min MVPA, 95% CI: 11.5, 33.5) and most sedentary (453.9 min, 95% CI: 417.7, 490.2) on Sunday. Most activity was accrued in the morning (before 12 PM) while the evening hours (3–11 PM) were spent ≥ 50% sedentary. Movement patterns suggest opportunities for promotion of activity and reduction in sedentary time on Sundays, in the evening hours, and for those with overweight or obesity.